IPTEK BAGI MASYARAKAT PRODUK SEPATU DI SRUNI SIDOARJO - Suparjo .; Randy Pratama Salisnanda (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
In this program, which became Partner 1 and Partner 2 is the hometown ofshoes in the village community Seruni Sidoarjo district, Mitra 1 with the ownersnamed Mr. Agus Supriyanto July is the shoe business is located at 202 Manggaroad 08 neighborhood, RW.02 Community Association, Seruni Sidoarjo, whilethe two partners with owner named Slamet Hariyanto is located in the shoebusiness Jumputrejo 09 neighborhood 03 Community Association SeruniSidoarjo. During this Partner 1 and Partner 2 introduce products into themarket rely solely on product sales by distributors who order goods to theiroutstanding auto brands is not the brand of the artisans themselves, but thebrand of the distributor. Not infrequently partner products in demand byconsumers, but because of the brand of the distributor, so that the artisansthemselves will never be known by the public. Besides the lack of skilled laborbecomes a serious problem for SMEs, where the village youth are moreinterested in working in an office or a factory that is around the village, whencompared to learning to be a shoe craftsman. During these partners get moremanpower from outside of Seruni Village. From the results of the fieldobservations and interviews with partners, there are three main things thatbecome the focus of development of SMEs, which includes aspects of productmarketing, product design aspects and aspects of human resource development.The third aspect is certainly a priority in improving the performance of SMEs.Each aspect of the development will provide assistance to partner activities,such as marketing aspects, partners will get help in the diversification ofmarketing tools to the marketing of products via the internet. Design aspects,relating to the design and brand advocacy in cooperation with the Departmentof product design ITATS so hope more partners are aware of the brand. Andthrough improved aspects of human resources, will be made with respect totraining and mentoring burst pattern and sewing workshop so that it can realizea skilled workforce and the competent.Keywords: Marketing Tools, Design, Brand, Competitiveness, SMEs.